Performance Analysis of Road and Bridge Planning Consultants in Highway Work in Banjarbakula - Ramadani, Wahid; Prasetia, Irfan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The results of planning often find errors in road handling methods and volume inaccuracies between planning and field conditions. This study aims to analyze the performance of planning consultants on indicators of planning documents, indicators of planning performance, and indicators of understanding of planning references. To determine the level of performance satisfaction used CSI method. As for knowing the performance that must be improved or less satisfactory, the IPA method is used. From the research results obtained based on the CSI method, Planning Document Indicators got 61.51% (Quite Satisfied), Planning Performance Indicators got 70.01% (Satisfied), and Indicators of Understanding of Planning References got 62.63% (Quite Satisfied). This study succeeded in identifying five factors that affect the performance of the planning consultant and need to be improved, namely 1) Conformity between the drawing documents, RKS, and Engineer Estimate, 2) The suitability of the type of personnel costs with project needs, 3) The suitability of the types of non-personnel costs with project needs, 4) Accuracy of data collection, and 5) The suitability of the method of calculating personnel costs with planning guidelines. The first strategy of the consultant is to commit to using competent personnel according to the qualifications listed. The second strategy of the consultant is to review the planned site carefully. Moreover, the last strategy is for consultants to work more optimally and effectively in construction projects.